2014
DOI: 10.1590/1807-3107bor-2014.vol28.0020
|View full text |Cite|
|
Sign up to set email alerts
|

Mouthrinse recommendation for prosthodontic patients

Abstract: Different reasons can contribute to classifying dental prosthesis wearers as high-risk individuals in relation to dental biofilm accumulation. These include a past history of oral disease, age and additional retentive areas. Other common complaints include inflammation and halitosis. Moreover, prosthesis replacement and prosthetic pillar loss are generally associated with caries and periodontal disease recurrence. Therefore, the present study undertook to make a critical review of the literature, aiming at dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
13
0
3
Order By: Relevance
“…Antiplaque oral rinses have proven to be effective against biofilms [17]. Rinses that contain chlorhexidine gluconate, as well as those that contain essential oils, while effective in plaque removal also have unwanted side effects.…”
Section: Current Strategiesmentioning
confidence: 99%
“…Antiplaque oral rinses have proven to be effective against biofilms [17]. Rinses that contain chlorhexidine gluconate, as well as those that contain essential oils, while effective in plaque removal also have unwanted side effects.…”
Section: Current Strategiesmentioning
confidence: 99%
“…Interestingly, although most physicians encourage patients to improve their oral hygiene to prevent dental problems, few physicians were intended to decrease the risk of developing sialolithiasis, and no study has ever reported the association between chronic periodontitis and sialolithiasis. Poor oral hygiene is believed to be largely responsible for an increased bacteria load in the oral cavity, and many studies have reported that improved oral hygiene largely decreases the risk of bacterial infection‐related comorbidities . Chronic periodontitis is highly associated with pathogenic bacteria in the oral microbiome .…”
Section: Discussionmentioning
confidence: 99%
“…Antiplaque oral rinses have been proven to be effective against biofilms [ 17 ]. While effective in plaque removal, rinses that contain chlorhexidine gluconate, as well as those that contain essential oils, have unwanted side effects.…”
Section: Chemical and Biological Methods To Control Oral Biofilmsmentioning
confidence: 99%